Caring Efficacy and Nurse Caring Behavior in Taking Care of Critical Patients - Lukmanulhakim Lukmanulhakim; Afriyani Afriyani; Ani Haryani (Universitas Airlangga, 2019)
Introduction: Critical patients have different needs compared to patients in other general inpatient wards, so they need extra treatments from a nurse. Nurse caring behavior gived through an approach in which nurses work by improving their concern to patients. However, it is influenced by caring efficacy in which a nurse is confident to express his or her caring to patients. The aims of this study were to identify the correlation between caring efficacy with nurse caring behavior in taking care of critical patients at dr. Dradjat Prawiranegara Serang Hospital in Banten ProvinceMethods: This is a quantitative study with employed a correlation study. The sample size comprised 66 Nurses of ER, ICU and HCU with total sampling technique. The instruments used are CES (Caring Efficacy Scale) to measure caring efficacy and CBA (Caring Behavior Assessment) to measure nurse caring behavior. Descriptive analysis using mean, standard deviation, percentage and frequency distribution. Meanwhile, inferential analysis used Pearson's Correlation.Results: The univariate analysis results showed the mean ± DS score of caring behavior is 87.6 ± 10.12. Meanwhile, the mean ± DS score of caring efficacy is 86.23 ± 8.74. Further, inferential analysis revealed a significant (p < 0.000) and moderate correlations (r = 0.448) between caring efficacy and nurse caring behavior.Conclusion: Higher of nurse's caring efficacy were followed by higher of nurse's caring behavior in taking care of critical patients. Findings can be used by academic as a prospective nurse and health professionals, to implement a concept of caring efficacy to improve caring behavior. Further research can be a focus on the nursing interventions based on nurses caring behavior to strengthen and increase in taking care of critical patients.